A Participatory Action Research (PAR) Approach in Digital Marketing Training to Improve Digital Literacy Skills - Dian Kurniasari; Purnamaningtyas Kusuma Dewi; Muhammad Faaiz Pandu Dewanata (Jurnal Pengabdian IPTEK, 2026)
The digital literacy gap in schools remains a real challenge, particularly in terms of the ability to use technology creatively and productively for academic purposes. Although access to technology is becoming more widespread, many teachers and students still lack the digital competencies needed to produce content and manage digital platforms independently. This Community Service (PkM) activity employs the Participatory Action Research (PAR) approach by Kemmis and McTaggart, following a cycle of (1) Plan, (2) Act, (3) Observe, and (4) Reflect, which positions teachers and students as active participants rather than mere beneficiaries. The activity aims to improve the digital literacy competencies of teachers and students at SMP Islam Ngemplak, Boyolali, through digital marketing training covering digital marketing concepts, graphic design using Canva, and video content production using CapCut. The effectiveness of the activity was measured using pretest and posttest instruments based on a Likert scale. The training results showed a highly significant increase in digital literacy competencies of 58.5%. A joint reflection at the end of the cycle resulted in concrete recommendations for the sustainable development of digital literacy.